Engagement in informal and formal cross-national diversity among local undergraduate students in Klang Valley, Malaysia - Yunus, Norzita; Tamam, Ezhar; Bolong, Jusang; Adzharuddin, Nor Azura; Amirrudin, Suraya (IKRAM Education, 2016)
The purpose of this study was to determine the level of engagement in informal and formal cross-national diversity among local undergraduate students in Klang Valley, Malaysia. A survey design was used to reach out to 1000 respondents who were selected using stratified sampling. The respondents were undergraduate students at three selected higher education institutions in Klang Valley. The findings indicate that the level of engagement for informal cross-national diversity is low and the level of engagement in formal cross-national diversity is moderate. The level of engagement for both types of diversity is not satisfactory and can further be improved to ensure that local students will benefit from cross-national diversity engagements.